2020
DOI: 10.3390/v12101112
|View full text |Cite
|
Sign up to set email alerts
|

HBV Prevention and Treatment in Countries of Central Asia and the Caucasus

Abstract: The countries of Central Asia and the Caucasus are linked by travel and trade, which is promoted by visa-free mobility across borders. Unfortunately, this migrant mobility has given rise to the transmission of various infections within this region. Overlaps in culture, tradition, and behavior among these countries provide opportunities to share experiences that have proven effective in controlling transmission. Here we present a review of hepatitis B virus (HBV) prevalence, prevention and treatment across Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Previous studies of the prevalence of viral hepatitis in Central Asian countries showed a decrease in the prevalence of viral hepatitis B in Kazakhstan [31]. We believe that this was due to the study of the prevalence of viral hepatitis in a specific cohort and not in the entire population of the country.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies of the prevalence of viral hepatitis in Central Asian countries showed a decrease in the prevalence of viral hepatitis B in Kazakhstan [31]. We believe that this was due to the study of the prevalence of viral hepatitis in a specific cohort and not in the entire population of the country.…”
Section: Discussionmentioning
confidence: 78%
“…In Southeast Asia, the estimation of birth‐dose vaccination coverage is only 34%, while three‐dose vaccination reaches 89% in 2019 74 . In Central Asia, the coverage of birth‐dose and three‐dose is 95%–99% respectively, which is an impressive achievement among developing countries 75 . With the availability and recommendation of neonatal vaccination, HBV vaccine coverage has been increasing in the past 5 years and more people in low‐income regions will be covered in the future.…”
Section: Prevention and Surveillancementioning
confidence: 99%
“…74 In Central Asia, the coverage of birth-dose and three-dose is 95%-99% respectively, which is an impressive achievement among developing countries. 75 With the availability and recommendation of neonatal vaccination,…”
Section: Preventing Hbv Infectionmentioning
confidence: 99%
“…Review on HBV prevention and treatment in Central Asian countries reported the estimated prevalence of HBV infection as 3.4%. 12 According to the recent systematic review on prevalence of HIV, HCV and HBV in Central Asian countries, the highest prevalence of HCV was reported in Kazakhstan with 90.1% among Intravenous Drug Users (IVDU); and HBV among IVDU to be 74.2% and 85.3% in two regions of the country. 13 Nationwide universal vaccination program was implemented in 1998 and is expected to decrease the burden of HBV infection in future decades.…”
Section: Introductionmentioning
confidence: 99%